Percepatan Struktur Modal Perusahaan Sektor Kesehatan Indonesia - Bandawaty, Euis; Nugraha, Nugraha; Disman, Disman; Sari, Maya (Image : Jurnal Riset Manajemen, 2023)
The aim of this research is to determine the influence of profitability, growth opportunities, liquidity, cash flow volatility, earning volatility and the magnitude of the acceleration of the capital structure of health sector companies in Indonesia in 2010-2022. The data analysis used is a dynamic capital structure model with a Partial Adjustment Model (PAM) approach which involves lag variables, determining factors of optimal capital structure and acceleration of capital structure in one equation. PAM model parameter estimation uses GMM with the aim of overcoming the problem of endogeneity. The GMM model test results show consistent, valid and unbiased. So the health sector company data is in accordance with the dynamic capital structure model, which is indicated by the coefficient value of the lag variable of 0.5821 which is smaller than 1 which is significant at an alpha of 0.05. The company's response to returning to an optimal capital structure is shown by an acceleration value (SOA) of 41.79%, with a time period of 1.3 years. Performance factors that have a negative influence on optimal capital structure are growth opportunities, liquidity and earnings volatility. Cash flow volatility has a positive influence. Meanwhile, profitability has no influence on optimal capital structure.